MENINGKATKAN KOMPETENSI GURU DALAM PROGRAM PEMBELAJARAN MELALUI MODEL PEMBINAAN CONTOH, LATIHAN, CONTROL DAN KERJA MANDIRI PADA SMAN 1 TOMMO - Arrang Arrang (Universitas Negeri Makassar, 2022)
This research is a school action research with stages that include planning, action, observation, and repeated reflection. The formulation of the problems in this study are: (1) Can the CLCK Coaching Model in the learning program increase the Teacher Competence of SMAN 1 Tommo?; (2) What is the teacher's response to CLCK coaching in the Learning Program to Improve Teacher Competence at SMAN 1 Tommo? The subjects in this study were the teachers of SMAN 1 Tommo consisting of 16 people, namely 4 boys and 12 girls. This study aims: (1) To improve teacher competence in learning programs with the Model, Practice, Control, and Independent Work (CLCK) coaching model; (2) To motivate teachers to be able to do their best in preparing learning programs. Based on the results of this school action research, it can be concluded that: (1) Through fostering the Example, Exercise, Control, and Independent Work (CLCK) model, teachers can improve their ability to develop learning programs, this can be seen in the first cycle activities, the average value is 72 or as much as 75% had prepared the learning program properly and correctly and in the second cycle the average value was 89 or as much as 91% had prepared the learning program properly and correctly; (2) CLCK coaching (Example, Exercise, Control, Independent Work) is very effective in the process of preparing learning programs for teachers, this can be seen from the teacher's response to the results of observations and questionnaires that the teacher gives a positive response to the model coaching activities Example, Exercise, Control, and Independent Work (CLCK). It is expected that the Principal in compiling learning programs (Syllabus and RPP) should apply the Example, Practice, Control, and Independent Work (CLCK) coaching model to subject teachers.